2020
DOI: 10.1002/esp.4924
|View full text |Cite
|
Sign up to set email alerts
|

Sand spit dynamics in a large tidal‐range environment: Insight from multiple LiDAR, UAV and hydrodynamic measurements on multiple spit hook development, breaching, reconstruction, and shoreline changes

Abstract: Sand spits with distal hooks have been well documented from coasts with low to moderate tidal ranges, unlike high tidal‐range environments. Datasets from 15 LiDAR and 3 UAV surveys between 2009 and 2019 on the Agon spit in Normandy (France), a setting with one of the largest tidal ranges in the world (mean spring tidal range: 11 m), combined with in‐situ hydrodynamic records between 2013 and 2017, highlight a three‐stage pattern of spit hook evolution. Stage 1 (2009–2013) commenced with the onshore migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 77 publications
1
16
1
Order By: Relevance
“…Over the course of the Holocene, this system has been affected by all three processes, with the addition of strong tidal influences. In contrast with observations in hyper-tidal areas, where the tidal range plays an important role in controlling changes in the barrier system due to high tide and storm events (Robin et al, 2020), there is little direct evidence of tidal influence in changes in the main ridges. The long-term migration of the spit/barrier system northwards under the influence of littoral sediment transport matches both field and modeling observations of changes in barriers associated with riverine inlets (e.g.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Over the course of the Holocene, this system has been affected by all three processes, with the addition of strong tidal influences. In contrast with observations in hyper-tidal areas, where the tidal range plays an important role in controlling changes in the barrier system due to high tide and storm events (Robin et al, 2020), there is little direct evidence of tidal influence in changes in the main ridges. The long-term migration of the spit/barrier system northwards under the influence of littoral sediment transport matches both field and modeling observations of changes in barriers associated with riverine inlets (e.g.…”
Section: Discussioncontrasting
confidence: 73%
“…Barrier systems, including spit and barrier complexes such as Inskip, are highly responsive to changes in sea level, storminess, and sediment supply (e.g. Raff et al, 2018: Robin et al, 2020). Over the course of the Holocene, this system has been affected by all three processes, with the addition of strong tidal influences.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we predict there would be an optimal slope range in which suitable sand lance habitat would occur (McFall 2019). Tidal currents play a strong role in spit formation (Robin et al, 2020), a shoreline feature where sand lance eggs are frequently observed. It is likely that intertidal spawning habitat is located near subtidal burying habitat (Haynes and Robinson 2011;Laugier et al 2015).…”
Section: Rationale For Environmental Predictor Selectionmentioning
confidence: 93%
“…Due to imperfect knowledge of the distribution of substrate, we also considered additional, proxy environmental variables that would capture geo-physical processes that influence the formation of 8 sandy beaches. We created a layer quantifying the distance to estuaries and to terrestrial sand sources, many of which are originally derived from glacial deposits, as they are known to contribute sediment to intertidal beaches and spits and drive water circulation in the Salish Sea (Peterson et al 1984;Mason et al 2018;Earle 2019;Robin et al 2020). A layer of shoreline slope was created as increases in slope are correlated with increases in sediment grain size.…”
Section: Rationale For Environmental Predictor Selectionmentioning
confidence: 99%
“…Shoreward migration process (in such wave dominated to mixed energy settings) of longshore bar under Mahanadi delta coast involves coalescence of individual bars to form large complex bars (300m to several km long) just before welding on to the shoreline [7,8,9]. Such welding sometimes results in the formation of large hook spits [10,4,11]. Bar welding mechanism can, thus, be an extremely important form of natural beach nourishment, attaining, in some cases, several millions of m3 in the course of a single welding event [12,13].…”
Section: Original Research Articlementioning
confidence: 99%